PENTINGNYA PEMAHAMAN BUDAYA DI SUATU NEGARA DALAM PEMASARAN PRODUK BERSKALA GLOBAL - Suhairi, Suhairi; Tondang, Grace Amalia; Devyana, Melati; Hasibuan, Rukiana (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Understanding the culture of a country is very important because when we market products that are not in accordance with market demand in that country, it is certain that the product will fail in the market, this is the basis for this research. In this study using descriptive qualitative research methods where all problems will be explained in depth and clearly, presented in the form of a literature study where the collection is done by literature review, reading articles, concluding and describing them in a paper. In this research it was found that understanding the culture of a country in marketing products on a global scale is very important because we have to know the things or goods that consumers need in a country that will have an impact on the success of our business in that country. This is because every country must have characteristics, styles, and habits that are innate and hereditary which have an impact on consumer behavior in that country